Promotional Video Design with Camera Movement Techniques on the Effectiveness of Merging Videos - Mieska Rachmadina Lubis; Khairani, Sumi; Rismayanti, Rismayanti (Journal of Computer Science and Informatics Engineering, 2022)
Promotion is one way to improve or introduce a product. The selection of promotional media for a product can provide more information to potential buyers, one of which is video. The author found a problem with one of the business actors who used video as a promotional medium and the video results were not effective or not as expected, designing a promotional video and finding criteria and camera movement techniques were thought to help the object to achieve effective and appropriate video results. It is hoped that the selection of the right video movement technique can also support harmony in the video merging process.